GAMBARAN PERCEIVED SOCIAL SUPPORT PADA IBU POSTPARTUM PRIMIPARA YANG MEMILIKI BODY IMAGE POSITIF - Panjaitan, Jovita Inez Alethea; Lentari, Fransisca Rosa Mira (Atma Jaya Catholic University of Indonesia, 2024)
Perceived social support (PSS) received by postpartum primiparous mothers are considered effective to support the whole forming process regarding body image satisfaction after giving birth. This research was aimed to get an overview of PSS in primiparous postpartum mothers with body image satisfaction using descriptive qualitative research methods involving three participants. The data collection process was carried out by using semi-structured interviews and analyzed using the thematic analysis method. The research results show that there are differences between how which PSS plays an important role in helping mothers perceived post partum’s body shape changes. Out of the four types of PSS, emotional/esteem support and belonging/companionship support are considered to play an important role in helping the process of forming a body image satisfaction for primiparous postpartum mothers. How they perceive the social support they received supports them in accepting, increasing self-confidence, and understanding their body shape after giving birth.